Techniques for treating slop oil in oil and gas industry: A short review. (1st November 2020) - Wang, Duo; Zhao, Ziqian; Qiao, Chenyu; Yang, Wenshuai; Huang, Yueying; McKay, Patrick; Yang, Dingzheng; Liu, Qi; Zeng, Hongbo
Graphical abstract: Highlights: Four commonly used slop oil treatment methods were systematically reviewed. Working principles and influencing factors of each method were introduced. Advantages and limitations of each treatment approach were discussed. Characteristics of slop oil have complicated effects on treatment efficiency. Combined techniques have great potential in future industrial applications. Abstract: Slop oil, a complex mixture of oil, water and fine solids, is extensively produced during exploration, production, and refining processes in oil and gas industry, which is undesired and has been a challenging issue. For example, steam-assisted gravity drainage (SAGD) is an effective technology for exploiting oil sands deposits. It provides a sustainable strategy to access deep reservoirs that cannot be tackled by surface mining. However, a large amount of slop oil generated in SAGD process is undesired. Treating the produced slop oil still faces many technical challenges mainly due to its complexity and commercial constraints. Much effort has been devoted to developing effective and cost-efficient treatment methods to handle the slop oil. In this work, we have systematically reviewed the working principles and interaction mechanisms of several commonly used slop oil treatment methods including chemical treatment, microwave irradiation, hydrocyclone and centrifugation methods. The influencing factors and practical applications of these methods (or their combination) are discussed. The effectiveness of the treatment techniques has been discussed in terms of emulsion separation efficiency and quality of separated phases. Some remaining challenges and perspectives for future research are also presented. This work provides an improved understanding of slop oil treatment, with useful implications for developing feasible, effective and cost-efficient techniques for treating slop oil in oil and gas industry.